2021
DOI: 10.1021/acsomega.0c02663
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermoelectric Properties of Poly(3-hexylthiophene) through the Incorporation of Aligned Carbon Nanotube Forest and Chemical Treatments

Abstract: Carbon nanotube/polymer composites have recently received considerable attention for thermoelectric (TE) applications. The TE power factor can be significantly improved by forming composites with carbon nanotubes. However, the formation of a uniform and well-ordered nanocomposite film is still challenging because of the creation of agglomerates and the uneven distribution of nanotubes. Here, we developed a facile, efficient, and easy-processable route to produce uniform and aligned nanocomposite films of P3HT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Figure S2a,b illustrates that the 40 nm spin-coated P3HT films were less resistant and were able to produce some S values in response to only higher doping levels (5–20 ppm of NO 2 ), but the S trend does not display a clear consistent decrease. In addition, at low doping levels, the S values of spin-coated P3HT could not be easily measured either due to low σ. Mardi et al reported the issue of not being able to measure TE properties of highly resistant pristine P3HT and P3HT doped with low dopant content . We propose that the NO 2 absorption is more efficient on a spin-coated film compared to a drop-cast film due to variation in thickness and morphology that lead to difference in the conditions of doping kinetics.…”
Section: Resultsmentioning
confidence: 89%
“…Figure S2a,b illustrates that the 40 nm spin-coated P3HT films were less resistant and were able to produce some S values in response to only higher doping levels (5–20 ppm of NO 2 ), but the S trend does not display a clear consistent decrease. In addition, at low doping levels, the S values of spin-coated P3HT could not be easily measured either due to low σ. Mardi et al reported the issue of not being able to measure TE properties of highly resistant pristine P3HT and P3HT doped with low dopant content . We propose that the NO 2 absorption is more efficient on a spin-coated film compared to a drop-cast film due to variation in thickness and morphology that lead to difference in the conditions of doping kinetics.…”
Section: Resultsmentioning
confidence: 89%
“…The fillers are usually carbon-based materials or inorganic-based materials. The most common fillers are carbon nanotubes [191] (see figure 16), graphene sheets [185,186], Bi 2 Te 3 nanowires [192], SnSe [193], and tellurium nanowires [194].…”
Section: Solution Processable Organic Thermoelectric Materials and De...mentioning
confidence: 99%
“…Very recently, Mardi et al 91 prepared nanocomposite films consisting of carbon nanotube forest (CNTF) and poly(3‐hexylithiophene) (P3HT). CNTF acted as a filler and improved the electrical conductivity of P3HT by forming a well‐interconnected network.…”
Section: Carbon‐based Thermoelectrics (Tes)mentioning
confidence: 99%